Antimicrobial Activity of Vigna unguiculata L. Walp Seed Oil - Ashraduzzaman, Mohammad; Alam, Mohammad Ashraful; Khatun, Shahanaz; Absar, Nurul (International Journal of Biotechnology for Wellness Industries, 2016)
The antimicrobial activity of three varieties of Vigna unguiculata L. Walp seed oil (LBS-1, LBS-2 and LBS-3) were investigated against five Gram positive bacteria (Bacillus megaterium, Bacillus subtilis, Sarcina lutea, Salmonella typhi and Staphylococcus aureus) and four Gram negative (Escherichia coli, Shigella dysenteriae, Shigella sonnei, Shigella shiga) and four fungi (Penicilium spp., Mucor spp., Candida albicans and Aspergillus fumigatius). The LBS-1 oil at the concentration of 400 µg/ disc showed the highest activity against Sarcina lutea (19±0.1 mm) than that of LBS-2 (14±0.3 mm) and LBS-3 (12±0.3 mm) oil whereas LBS-3 oil showed highest activity against Staphylococcus aureus (16±0.1 mm) than that of LBS-1 (10±0.6 mm) and LBS-2 (13±0.4 mm) oil. All the three oils are active against the three tested fungi namely Penicilium spp., Mucor spp. and Candida albicans but showed no sensitivity against Aspergillus fumigatius.